The effects of exercise-based injury prevention programmes on injury risk in adult recreational athletes: a systematic review and meta-analysis - Liddle, N.; Taylor, J. M.; Chesterton, P.; Atkinson, G. (Sports Medicine, 2024)
Key Points: